Análise e dimensionamento de uma viga de ponte ferrovíaria em concreto protendido - Souza, Anna Caroline Fermino de (2015)
This paper has as its main goal to design and analyze a railway bridge stringer in prestressed concrete. This kind of structure, called special art of work, is very important to railway. In order to determine the ideal track to the train, one wants to look the lower longitudinal slopes, in the same way it looks for the longest curve radii, ensuring the best way to develop the train speed. The base beam used in this study already exists in a bridge which details was presented in the ESTRUTURA magazine, 93th edition, 1980, made by Fernando Uchoa Cavalcanti Engineer. Initially its dimensions and the technical features, as the concrete strength (fck = 28 MPa), reinforcing steel (CA-50), prestressing (CP-175 RB) and the train-type (TB-32 from Brasilian standard NB-7) were taken to make the first verification of the structure using the principles of the Brasilian Standard NBR 6118:2014 and the PCI/ACI Simplified Method. The Concise Beam 4.59m software was used in order to help with this verification. After that, when checked at the Ultimate Limit State (ULS) and Serviceability Limit State (SLS), it was seeing that the results were inconclusive, even though reinforcing steel was being used. So, in order to make a new analysis of the beam, a new design were made, maintaining its dimensions, but changing the concrete strength (fck = 40 MPa), the prestreessing (CP-190 RB), the train-type (TB-270) and inserting a new reinforcing steel (CA-50). With these, after checking again at the ULS and SLS, the beam had satisfactory results, which allows us to conclude that since there were updates in all the standards involved (specially because of the train-type), even if the design was made nowadays, several modifications in its reinforcements and characteristics would be needed in order to make it satisfactory to the premises of the ULS and SLS.